Новітні роботи Львівської обласної експедиції - Мацкевий, Л.Г.; Гнатюк, Р.М.; Панахид Г.І. (Археологічні дослідження в Україні, 2009)
In burial cliff grotto Lviv XIII the excavations were ongoing on the area of 5 м2 (Early Palaeolithic period), and in Romaniv I trenches were laid at the area of 14 м2 (Mesolithic, the 13th—14th c. and the 20th c.). Yalivtsi I settlement of Mesolithic period was discovered, and the protective work was conducted at five sites in Lviv (Lviv II and Lviv VII) and in Mykolaiv Region (Pryima I — grotto, Rozvadiv II, and Veryn V).